Numerical method for modeling of acoustic waves propagation - DYKAS, Sławomir; WRÓBLEWSKI, Włodzimierz; RULIK, Sebastian; CHMIELNIAK, Tadeusz (Archives of Acoustics, 2010)
In this paper, numerical results of modeling of acoustic waves propagation are presented. For calculation of the acoustic fluctuations, a solution of the full non-linear Euler equation is used. The Euler equations are solved with the use of a numerical scheme of third-order accuracy in space and time. The paper shows a validation process of the described method. This method is suitable also for an aerodynamic noise assessment on the basis of unsteady mean flow field data obtained from a CFD calculations. In such case this method is called a hybrid CFD/CAA method. The proposed method is numerically decoupled with CFD solution, therefore the information about the mean unsteady flow field can be obtained using an arbitrary CFD method (solver). The accuracy of the acoustic field assessment depends on the quality of the CFD solutions. This decomposition reduces considerably the computational cost in comparison with direct noise calculations. The presented Euler acoustic postprocessor (EAP) has been used for modeling of the acoustic waves propagation in a cavity and in the flow field around a cylinder and an aerodynamic profile.